IMPACTOS DOS GASTOS PÚBLICOS SOCIAIS NO CRESCIMENTO DOS MUNICÍPIOS: EVIDÊNCIAS PARA O PARANÁ COM DADOS EM PAINEL (Publicatio UEPG: Ciências Sociais Aplicadas, 2023)
This research aimed to verify the impacts that public social spending causes on the growth of municipalities in Paraná between 2013 and 2019. For this, public social spending on social assistance, health, education, culture and urbanism were regressed against GDP of the municipalities of Paraná by the fixed effects model of panel data. All public social spending was expected to contribute positively to growth. However, as verified, only the social assistance, health and education functions were significant. In other words, only these three functions have an impact on the growth of municipalities. In addition, the three presented positive coefficients, as expected. This answer is also in agreement with what was found by other authors such as Braatz, Gonçalves and Fochezatto (2019) and Andrade, Teixeira and Fortunato (2014).